The spiritual man exists - Uríbarri, Gabino (Razón y fe, 2018)
Many readings and interpretations have been made and will be made of the resignation of Benedict XVI from the pontificate. In this brief and substantial text, without falling into one-sidedness, a reading is made from the human and spiritual path of the former Pope Ratzinger.